Religion and cancer prevention: study protocol for a systematic review - Hans-Helmut König; André Hajek; Benedikt Kretzler; Linéa Brandt (BMJ Open)
Introduction Several studies explored a relationship between religiousness and the utilisation of cancer screenings, as religious people may obtain an increased social network or could have certain personality traits that enhance screening use. To the best of our knowledge, there is no systematic review that sums up the evidence gained from research on that relationship. Thus, our review aims to appraise the findings of observational studies regarding that relationship. Its findings may be useful in addressing specific target groups to increase ineffectively the low cancer screening rates.Methods and analysis Employing a predefined search algorithm, three online databases (CINAHL, PsycInfo and PubMed) will be searched. In addition, the bibliographies of the studies included in our review will be searched through manually and independently by two reviewers. We are looking for observational studies (both cross-sectional and longitudinal) which examine the association between religion and cancer screening utilisation. However, studies regarding specific samples (as ethnic minorities or religious sects) will be excluded. We expect that the studies examine various dimensions of religion, such as religious attendance or religious intensity. We will extract data that describe methodology, sample characteristics and the findings concerning our object of investigation. Moreover, a quality assessment will be performed. Two reviewers will independently select the studies, extract the data and assess the studies’ quality. Disagreements will be dissolved by discussion or by inclusion of a third party. The findings will be presented narratively in text and tables. If possible, a meta-analysis will be carried out.Ethics and dissemination As no primary data are collected, the approval from an ethics committee is not required. Our review will be published in a peer-reviewed, scientific journal.PROSPERO registration number CRD42021229222.